PENGAJARAN TENTANG SIKAP HIDUP ORANG PERCAYA BERDASARKAN 1 PETRUS 3:8-12 - Evi Tobeli; Hana Nugraeni Oktiyati (JURNAL PENABIBLOS, 2024)
Life attitude can be reflected in someone's life every day. To be able to have the right attitude to life, it is necessary to learn and emulate Jesus' attitude in various aspects. Jesus has provided many inspirations and examples of life for believers. A good attitude to life like sweet fruit can be enjoyed by others. According to the Apostle Peter in letter 1 Peter 3: 8-12, believers should have three attitudes of life, namely loving others, not reprimanding with verbal abuse and saying things that bless. To be able to see a good day, believers need to love life, namely the attitude of faith that always looks the best in every situation, being positive about life means doing the best in his life that is able to bless everyone and not say bad things about others. In addition, believers must guard their tongues, because there are many problems of life caused by false words or evil words and deceptive speeches. It does not have a negative effect on other people who hear these words, but can also have a negative impact on yourself